Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec - Backhouse, Constance (Labour / Le Travail, 1999)
The article reviews the book, "Power, Place and Identity: Historical Studies of Social and Legal Regulation in Quebec," edited by Tamara Myers, Kate Boyer, Mary Anne Poutanen and Steven Watt.